Development and evaluation of controlled porosity osmotic pump tablet of losartan potassium - Kausar Sulthana; G.Ganesh Kumar (International Journal of Pharmacy and Analytical Research, 2017)
The aim of the present work was to prepare and evaluate controlled porosity osmotic pump tablets of Losartan potassium to prolong the release of drug oral administration. Losartan potassium is an anti -hypertensive drug and it acts as an angiotension II receptor antagonist. The tablets were prepared by the wet granulation method using mannitol as an osmogen and polymers like polyox N -80, polyox N-205 at different concentrations. The tablets were coated with opadry CA upon contact with water it results in an in situ formation of a micro porous structure. Total twelve (F1-F12) were formulated and the tablets were evaluated for various parameters such as compatibility studies, drug content, weight variation, hardness, thickness, friability, in vitro drug release studies and release rate kinetics. The drug-polymer interaction was also studied by conducting FTIR. The in vitro release kinetics studies reveal that all formulations fits well with Zero order, followed by Korsmeyer -Peppas and the mechanism of drug release follows super case II transport. After analysis of different evaluation parameters and drug release kinetics, formulation code F9 was selected as a promising formulation for delivery of Losartan potassium as a controlled porosity osmotic pump tablet wit h 99.82 % in vitro drug release at 24th hour. The stability studies were carried out at 40°C/75% RH for 90 days. There was no significant change in the physical property during the study period.